Development of a Digital Business Laboratory Model for the Faculty of Islamic Economics and Business at the State Islamic Universities: The Experience at the State Islamic University of Sunan Gunung Djati Bandung - Sobana, Dadang Husen; Yusup, Deni Kamaludin; Hartati, Neneng; Yulandri, Elsa; Budiana, Nuraini Qolbi Shafira (Journal of Ecohumanism, 2024)
Currently, digital business laboratories are one of the most important tools for student skills in university business. However, based on initial searches, a digital business laboratory has yet to be found within the State Islamic Universities (PTKIN). This research aims to analyze the digital business laboratory development model at PTKIN. This research uses research and development methods with a qualitative-comparative approach. This research concludes that this digital business laboratory plays a role in forming Bachelor of Economics who are adaptive, creative, and have strong digital business skills. Not only that, but digital business laboratories must uphold the function of higher education. The development and management of such a complex laboratory ultimately produces output and outcomes for students and the community, government, and stakeholders involved in laboratory operations. Mono-disciplinary, interdisciplinary, and multi-disciplinary approaches are alternative development patterns to equip students with excellent knowledge and skills. Through this strategy, a digital business laboratory development model was created by carrying out three programs, namely the internship program, partnership program, and empowerment program. Thus, this research is expected to contribute fully to advancing students, universities, government, and society.